THEORETICAL AND METHODOLOGICAL PRINCIPLES FOR RESEARCH POPULATION’S LIVING STANDARDS - Tomchuk-Ponomarenko , Nataliia (Socio-economic relations in the digital society, 2021)
Abstract. The article considers theoretical approaches to determining the living standards of the population in the system of socio-economic relations. The modern understanding of the standard of living through the prism of the evolution of scientific views is substantiated. The author’s understanding of the standard of living and wellbeing of the population is revealed, the place of these categories in the system of social and economic relations is determined. Approaches to the analysis of living standards with the identification of their advantages and disadvantages are analyzed and generalized. The conceptual apparatus of the category «standard of living», the ratio of the categories «welfare», «quality of life», «way of life» have been improved; the definition of the category «social welfare» as a socio-economic category, which includes economic, social, institutional, environmental, psychological, cultural and historical characteristics of living conditions, to identify the main trends in society and develop practical tools for further socio-economic growth countries. The term «well-being» in the study of well-being, researchers often refer to a person’s feelings and perceptions of health and personal happiness, which distinguishes it from other components of well-being. The study of living standards through the prism of modern processes of economic growth is taking into account certain categories (objectivity, subjectivity, levels and regimes) with an emphasis on ensuring balance (sustainability of welfare). Various methods of welfare assessment have been proposed in foreign and domestic science, the generalization of which allowed to identify four modern approaches to its analysis — based on the adjusted value of Gross Domestic Product, weighing indicators, integrated assessment and sociological assessments. It remains important to establish a holistic methodology for assessing living standards in order to identify its relationship with economic, including financial, determinants at different institutional and spatial levels — the state, region, community, household. Keywords: welfare, standard of living, living conditions, poverty, way of life, situation of the population. JEL Classification D63, F66, I31 Formulas: 0; fig.: 0; tabl.: 0; bibl.: 16.